Changes of potential shorty-chain fatty acids producing bacteria in the gut of patients with spinal cord injury: a systematic review and meta-analysis - Zhong, Zaowei; Fan, Fei; Lv, Junqiao; Wang, Zhiqiang; Wang, Beiyang; Deng, Chen; Sun, Lin (Frontiers in Microbiology, 2025)
Gut bacteria that potential produce short-chain fatty acids (SCFAs) influences the recovery of motor function in the host in patients with spinal cord injury (SCI). We aimed to conduct a review and meta-analysis of the literature on gut microbiota in SCI patients. Following the Preferred Reporting Project for Systematic Review and Meta-Analysis (PRISMA), we searched Embase, PubMed, Cochrane Library, Web of Science (WOS) and ClinicalTrials.gov. The search period was from inception to March 31, 2024. We reported standardized mean differences (d) with 95% confidence intervals (CI) and used funnel plots and Egger tests to assess publication bias. The subacute of SCI data set revealed the microflora changes in the subacute phase, and meta-analysis summarized the changes in the chronic phase. Eleven studies (720 participants) were included, 2 phyla, 1 order, and 14 genus meta-analyses performed. No substantial heterogeneity was observed, and significant publication bias was not found among the studies included. In the subacute phase of spinal cord injury, the relative abundance of Bacteroidetes, Clostridiales, Faecalbacterium, Ruminococcus, Coprococcus, Lachnospira, Dorea, Prevotella, Roseburia, Atopobium, Bifidobacterium, Bacteroides, and Blautia increased. Firmicutes and Lactobacillus decreased. In the chronic phase, Firmicutes decreased in the SCI group. Bifidobacterium, Bacteroides, Blautia, and Eubacterium were found to have a higher average proportion of abundance in patients with SCI compared to non-SCI persons, and Clostridiales, Ruminococcus, Faecalbacterium, Coprococcus, and Lachnospira showed a lower relative abundance in SCI. The genus of potential SCFAs-producing bacteria is lower in the chronic phase of spinal cord injury than in the subacute phase, and gut dysbiosis is present in both the subacute and chronic phases.